Human Uptake of Eggshell Powder as an Alternate Source of Calcium (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Calcium (Ca) plays important structural and physiological roles in our body. Usually, our body meets up its Ca need from dietary sources. In developing countries like Bangladesh, most of the people cannot afford Carich foods. So, Ca supplements are generally prescribed to deficient individual that usually costs high. It is, therefore, necessary to find out an alternative and cheap source of Ca supplement especially in Bangladesh. Considering the above facts, the main focus of this study was to explore the possibility of using the egg shell as a source of Ca. In his study, discarded eggshells were collected, washed, decontaminated properly and ground to a fine powder. Washing with tap water followed by 10 min boiling completely decontaminated the eggshells. On an average 3.45, 5.91, 4.5 and 4.55 g of eggshell powder (ESP) per shell were obtained from a domesticated fowl, domestic duck, white leghorn, and rhode island red, respectively. Particle size was measured using scanning electron microscope and the size ranged between 3.47-5.94 μm. The Ca contents were found as 38.65, 35.0, 24.85 and 35.73 g in domesticated fowl, domestic duck, white leghorn, and rhode island red, respectively per 100 g of ESP. Taking daily Ca requirements into account, we observed that powder from almost half of an eggshell is sufficient to fulfill the daily Ca need. The amount of magnesium (Mg) in 100 g ESPs was found to be 45.37, 32.48, 45.17 and 45.27 mg and that of iron (Fe) was 35.07, 33.47, 31.91 and 33.06 mg in domesticated fowl, domestic duck, white leghorn, and rhode island red, respectively. Various toxic heavy metals such as chromium (Cr), lead (Pb) and arsenic (As) contents remained below the detection level in ESP samples. Organoleptic tests revealed that the ESP does not have any objectionable effects on the texture and flavor of ESP-fortified foods and juice. These results suggested that the ESP can be used as an alternative and important cheap source of Ca and other beneficial micronutrients for human being. However, it is necessary to create the awareness and public perception regarding the use of EPSDhaka Univ. J. Pharm. Sci. 18(2): 249-255, 2019 (December)